(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In addition to the check-lists of the Italian fauna , specific information is given on 35 species of Gelechiidae which are new or the first reliable records for the country. Further 14 species which were already published earlier are discussed and partially deleted from the Italian fauna. 41 species of the entire Gelechiidae fauna of ltaly were not examined by the authors and are listed separately.